2015
DOI: 10.1002/pros.23106
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β controls autophagy by modulating LKB1-AMPK pathway in prostate cancer cells

Abstract: BACKGROUND Glycogen synthase kinase 3β (GSK3B, GSK-3β) is a multi-functional protein kinase involved in various cellular processes and its activity elevates after serum deprivation. We have shown that inhibition of GSK-3β activity triggered a profound autophagic response and subsequent necrotic cell death after serum deprivation in prostate cancer cells. In this study, we dissected the mechanisms involved in GSK-3β inhibition-triggered autophagy. METHODS Prostate cancer PC-3 and DU145 cells were used in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 57 publications
(80 reference statements)
4
48
0
Order By: Relevance
“…AMPK signaling inhibitor, dorsomorphin (compound C) 2HCl (Selleck Chemicals, Houston, TX, USA), was dissolved in sterile double-distilled water, whereas GSK3b inhibitor, TDZD-8 (Selleck Chemicals), and glycolysis inhibitor, 2-deoxy-D-glucose (2-DG; Selleck Chemicals), were dissolved in DMSO. Anoikisresistant PC-3 or DU145 cells were treated with 4 or 2 mM dorsomorphin, respectively, for 24 h (Supplemental Information 3), and anoikis-resistant PCa cells were treated with 10 mM TDZD-8 for 24 h or 10 mM 2-DG for 48 h (25,26). Isometric double-distilled water or DMSO were used as negative control (NC).…”
Section: Treatment Of Ampk Gsk3b and Glycolysis Inhibitorsmentioning
confidence: 99%
“…AMPK signaling inhibitor, dorsomorphin (compound C) 2HCl (Selleck Chemicals, Houston, TX, USA), was dissolved in sterile double-distilled water, whereas GSK3b inhibitor, TDZD-8 (Selleck Chemicals), and glycolysis inhibitor, 2-deoxy-D-glucose (2-DG; Selleck Chemicals), were dissolved in DMSO. Anoikisresistant PC-3 or DU145 cells were treated with 4 or 2 mM dorsomorphin, respectively, for 24 h (Supplemental Information 3), and anoikis-resistant PCa cells were treated with 10 mM TDZD-8 for 24 h or 10 mM 2-DG for 48 h (25,26). Isometric double-distilled water or DMSO were used as negative control (NC).…”
Section: Treatment Of Ampk Gsk3b and Glycolysis Inhibitorsmentioning
confidence: 99%
“…An increase of intracellular glucose storage and induction of autophagy have been demonstrated in 9-ING-41-treated renal cancer cells (20). Inhibition of GSK-3 triggers an autophagic response in prostate (31), pancreatic (32) and renal (20) cancer. Pal et al (20) have demonstrated that GSK-3 inhibition by 9-ING-41 affects energy homeostasis and triggers a pro-survival autophagic response in renal cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Several reports have suggested that this compensatory autophagy is induced by a stress response elicited during proteasome impairment. Mitochondrial ROS production and depletion of amino acids during proteasome dysfunction cause the activation of autophagy through sensing via AMPK and mTORC1, respectively (Jiang et al, ; Min et al, ; Sun et al, ). Proteasome impairment also induces endoplasmic reticulum (ER) stress, which then triggers transcriptional up‐regulation of autophagy‐related genes (Brüning, Rahmeh, & Friese, ; Høyer‐Hansen & Jäättelä, ; Senft & Ronai, ).…”
Section: Introductionmentioning
confidence: 99%